How to Increase Job Satisfaction Through Employee Career Development at PT GMF Aero Asia Tbk. - Budi Krisna Lelmalaya; Anoesyirwan Moeins; Marhalinda Marhalinda (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to examine the influence of transformational leadership, organizational justice, and competence on job satisfaction through employee career development at PT GMF Aero Asia Tbk. This study uses a descriptive quantitative approach. The data was taken through a questionnaire and analyzed by the SEM method of the LISREL 8.80 application. The sample was taken using simple random sampling, and the sample size using the Slovin formula was generated by 318 staff-level employee respondents. This study provides that transformational leadership and competence have a positive and significant effect on career development, organizational justice has a positive but not significant effect on career development, and transformational leadership, organizational justice, and competence have a significant positive effect on job satisfaction. Simultaneously, the results show transformational leadership, organizational justice, and competence at the same time have a positive and significant effect on career development. R2 on career development is 61%. R2 on job satisfaction is 81%, Career development is classified as a partial mediation variable.